2021
DOI: 10.1186/s13195-021-00850-3
|View full text |Cite
|
Sign up to set email alerts
|

Network medicine links SARS-CoV-2/COVID-19 infection to brain microvascular injury and neuroinflammation in dementia-like cognitive impairment

Abstract: Background Dementia-like cognitive impairment is an increasingly reported complication of SARS-CoV-2 infection. However, the underlying mechanisms responsible for this complication remain unclear. A better understanding of causative processes by which COVID-19 may lead to cognitive impairment is essential for developing preventive and therapeutic interventions. Methods In this study, we conducted a network-based, multimodal omics comparison of COVI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 125 publications
(200 reference statements)
7
93
0
Order By: Relevance
“…Likewise, hsa-miR-298 can bind the 5′UTR region, and its down-regulation in Alzheimer disease has been demonstrated. According to previously published papers, the binding of miRNAs to the viral genome may reduce the levels of free miRNAs in the cell, and it has been recently reported that COVID patients may develop an Alzheimer’s-like disease [ 51 ]. Moreover, the ability of hsa-miR-3941 to target the SARS-CoV-2 3′-UTR was recently validated in vitro by gene reporter assays [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, hsa-miR-298 can bind the 5′UTR region, and its down-regulation in Alzheimer disease has been demonstrated. According to previously published papers, the binding of miRNAs to the viral genome may reduce the levels of free miRNAs in the cell, and it has been recently reported that COVID patients may develop an Alzheimer’s-like disease [ 51 ]. Moreover, the ability of hsa-miR-3941 to target the SARS-CoV-2 3′-UTR was recently validated in vitro by gene reporter assays [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the COVID-19, it is highly likely that impaired retinoid signaling has an important role in the development of in the nervous system-related symptoms [170] , [171] .In the course of COVID-19, the involvement of these areas of the nervous system where retinoid signaling is normally highly intense, may likely suggest a cause-and-effect association that needs further investigation. In addition to the mild symptoms and severe clinical picture of acute illness, neuropsychiatric manifestations such as autism, dementia, schizophrenia, depression, and insomnia may occur as post-COVID syndromes that can well be, at least partially, due to impaired retinoid signaling [172] , [173] .…”
Section: Cns Involvement and Retinoid Signaling Disorder Incovid-19mentioning
confidence: 99%
“…Several studies have described the presence of brain lesions as responsible of auditory impairment ( 9 11 ), supporting the hypothesis that SARS-CoV-2, which has neuro-invasive characteristics, might determine a central hearing loss in COVID-19 patients both in the active phase and during recovery ( 12 ). It has been shown that the virus can spread from neuroepithelium to the olfactory bulb to the brain ( 13 15 ), causing loss of smell ( 16 ), persistent cough after pneumonia resolution ( 17 ), memory deficit ( 18 ), and neurocognitive problems ( 19 ).…”
Section: Introductionmentioning
confidence: 99%